2020
DOI: 10.1111/vcp.12865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hematologic, biochemical, and blood gas variables in stored canine packed red blood cells, and the impact of storage time on blood recipients

Abstract: Background: Canine packed red blood cells (pRBCs) can be stored under refrigeration for several days; however, cellular metabolism remains active inside the units, thus producing substances that affect their quality. Objectives: We aimed to evaluate hematologic, biochemical, and blood gas variable alterations that occur in canine pRBCs during storage, and their effects on recipient clinicopathologic parameters. Methods: The study was conducted in two phases. In phase I, 15 pRBC units containing CPDA-1 were sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Similar to previous studies, our study demonstrated an increase in lactate concentrations and pCO 2 during storage. 14 , 28 , 29 , 30 During storage, erythrocyte metabolic function is more dependent on anaerobic metabolism, which requires the conversion of intra‐cellular pyruvate to lactic acid. 28 , 31 During storage, the erythrocyte intracellular concentration of 2,3‐diphosphoglycerage (2,3‐DPG) decreases, which reduces RBC oxygen carrying capacity and promotes anaerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to previous studies, our study demonstrated an increase in lactate concentrations and pCO 2 during storage. 14 , 28 , 29 , 30 During storage, erythrocyte metabolic function is more dependent on anaerobic metabolism, which requires the conversion of intra‐cellular pyruvate to lactic acid. 28 , 31 During storage, the erythrocyte intracellular concentration of 2,3‐diphosphoglycerage (2,3‐DPG) decreases, which reduces RBC oxygen carrying capacity and promotes anaerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 28 , 29 , 30 During storage, erythrocyte metabolic function is more dependent on anaerobic metabolism, which requires the conversion of intra‐cellular pyruvate to lactic acid. 28 , 31 During storage, the erythrocyte intracellular concentration of 2,3‐diphosphoglycerage (2,3‐DPG) decreases, which reduces RBC oxygen carrying capacity and promotes anaerobic metabolism. 32 , 33 In both canine and human blood products, lactate begins to increase within 7 days of storage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before using, blood components usually are visually inspected and bacterial infection should be suspected when there is a discoloration of the component, hemolysis of the upper layers of red blood cells, or presence of visible clots. If such signs are detected, a bacteriological examination of this unit should be provided to determine if contamination occurred (Rodrigues et al, 2020).…”
Section: Analysis Of Recent Researches and Publicationsmentioning
confidence: 99%